Kebijakan Penegerian Madrasah pada Kementerian Agama RI: Sebuah Telaah Deskriptif - Khanali, Ahmad (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2023)
This article describes the background to the uneven access and quality of madrasah education, with the condition of the existence of only 5% of public madrasas while most of the rest are private madrasas. This condition reflects the high role of the community in the implementation of madrasa education and the still not optimal management of madrasas by the government. The emergence of a madrasa nationalization policy with the hope that state madrasas could become reference madrasas or model madrasas for other madrasas in their vicinity. The author's goal in compiling this policy paper is to describe the extent to which the madrasah nationalization policy is needed and how the nationalization policy strategy is carried out. In order to ensure that this manuscript is able to answer the above objectives, the authors use a descriptive analysis approach. The madrasa nationalization policy carried out has a significant urgency in improving the quality of madrasah education and has been proven empirically from various studies. In addition, the madrasa nationalization policy also has several benefits. Madrasa nationalization policies can be carried out in tandem with the establishment of madrasas which are organized by the Government or the community with reference to the Regulation of the Minister of Religion Number 90 of 2013 concerning Implementation of Madrasa Education.